Functional Characterization of Calreticulin in Invasive Human Breast Cancer - Zamanian, Mohammedreza (2011)
Breast cancer is the second leading cause of cancer deaths in women. Invasion is an important hallmark of cancer that confers the ability of cells to metastasize and spread to other sites of the body. Thus, finding novel molecular biomarkers of invasion and metastasis is integral for the advancement of breast cancer management. Calreticulin (CRT) is a multifunctional endoplasmic reticulum protein. CRT is a major player in intracellular calcium storage and transfer. It also plays a role in other cellular functions such as chaperoning and adhesion. Previous studies have tried to correlate CRT overexpression with tumorigenesis. For example, CRT has been postulated to be a contributing factor in the role of thrombospondin-1 in invasion. CRT has also been shown to interact with Estrogen Receptor-α and revert hormone-independent inhibition of breast cancer cell invasion. The main objective of this study was to functionally characterize the possible role(s) of CRT in breast cancer cell invasion phenotype. The specific objectives of the study were to (i) compare CRT protein expression in different invasive states of human breast cancer tissues, (ii) determine CRT-dependent migratory and invasive potentials of breast cancer cells and (iii) establish the CRT-dependent gene regulatory pathways. To confirm the CRT-associated breast cancer pattern of expression, immunohistochemistry analysis of formalin fixed paraffin-embedded breast cancer tissues was conducted. Using siRNA technology, we developed a CRT-knockdown model of MCF7 breast cancer cell line. We evaluated the CRT genotype-phenotype correlations using migration and transwell invasion assays as well as cell-cycle analysis. Western blotting and quantitative-real time polymerase chain reaction (qRT-PCR) assays were used to determine the level of CRT expression, while ß-actin was used as the housekeeping gene. Finally, microarray-based global gene expression profiling was conducted to dissect the possible CRT pro-invasive regulatory pathways. Meta-analysis of the immunohistochemical results confirmed that the expression of CRT was significantly higher (p<0.05) in the stromal compartments of malignant tissues as compared to those from non-malignant samples. Subsequently, successful siRNA-mediated CRT gene silencing in MCF7 cells was achieved and this was confirmed both at mRNA and protein levels by qRT-PCR and western blot, respectively. Consequently, using migration and transwell invasion assays, the migratory and invasive potentials of CRT-deficient cells were compared to CRT-expressing cells. A significant loss in the migratory and invasive potentials was evident in CRT-deficient cells (p<0.05). Finally, global gene expression profiling successfully identified various gene networks involved in CRT breast cancer signaling. Hence, besides confirming CRT overexpression in invasive breast cancer tissues, we demonstrated the CRT-dependent pro-invasive potential and signaling pathways in vitro. Future work will focus on defining the mechanistic role of invasion and characterizing the possible CRT-dependent molecular targets as diagnostic, prognostic and therapeutic biomarkers of breast cancer.